Significant Effect of Valproate Augmentation Therapy in Patients With Schizophrenia: A Meta-analysis Study. Issue 4 (January 2016) - Tseng, Ping-Tao; Chen, Yen-Wen; Chung, Weilun; Tu, Kun-Yu; Wang, Hung-Yu; Wu, Ching-Kuan; Lin, Pao-Yen
Abstract : Abstract: Valproate is an anticonvulsant, which is also widely used for treating psychiatric disorders. Some clinical trials have demonstrated benefits of valproate augmentation therapy in schizophrenia. Previous meta-analysis showed inconsistent findings because of limited literature at that time. The aim of this study is to update the newer published data by conducting a meta-analysis of clinical efficacy of valproate augmentation therapy in patients with schizophrenia or schizoaffective disorder. Data sources include electronic research through platform of PubMed. Study eligibility criteria, participants, and interventions were as follows: the inclusion criteria included articles discussing comparisons of the treatment effect in schizophrenic patients treated with antipsychotic augmented with valproate and antipsychotics with/without placebo; articles on clinical trials in humans. The exclusion criteria were case reports or series and nonclinical trials. We compared the effect between antipsychotic treatment with valproate augmentation and antipsychotic monotherapy. Data from clinical trials were pooled by random-effects model, and possible confounding variables were examined through meta-regression and subgroup analysis. Data from 11 articles including 889 patients were included into current meta-analysis. We found patients treated with antipsychotics with valproate augmentation showed significantly more improvement in total psychopathology than those treated with antipsychotics only ( P  = 0.02). Results from open trials, but not from randomized controlled trials ( P  = 0.20), showed significant improvement ( P  = 0.01). In addition, the significance only persisted in the studies conducted with a shorter treatment duration ( P  < 0.001) rather than longer treatment duration ( P  = 0.23). There is no difference in the dropout rate between valproate augmentation and antipsychotic treatment only ( P  = 0.14). We could not perform a detailed meta-analysis for every category of antipsychotics, long-term effect, and safety profiles of valproate augmentation therapy in maintenance treatment, safety in pregnant patients, and subtype of schizophrenia. Our meta-analysis highlights the significantly better treatment effect with valproate augmentation therapy in patients with schizophrenia or schizoaffective disorder, and provides important evidence for supporting the practice of valproate augmentation therapy in these patients. Abstract : Supplemental Digital Content is available in the text